Talent Management at Meira Visi Persada Foundation - Mariana, Diah; Rachmawati, Meida (International Journal of Law Social Sciences and Management, 2024)
The research seeks to understand the importance of Talent Management at the MVP Foundation. The method used in this study is a descriptive method with a qualitative approach. The data sources used are primary and secondary data. Data collection techniques include observation, interviews, and documentation. The research instruments are the researcher, interview guidelines, and field notes. Talent management is key to the success of Meira Visi Persada (MVP) Foundation, focusing on human resource development and innovation. MVP's talent management strategy includes the recruitment, development, and retention of talented employees, and managing them to support growth and productivity. A careful recruitment process ensures alignment with the foundation's mission, builds a competent team, and reduces turnover. Continuous training programs enhance staff skills, motivation, and engagement, positively impacting productivity and the achievement of the foundation's mission.